A Story of State Transformation in the Global South: Limited Statehood and Governance in Post-Syria Lebanon - Jalit, Jodor (AUC Knowledge Fountain, 2024)
This research thesis analyzes security governance in areas of limited statehood in the context of state transformation. Specifically, it examines the impact of the 2005 Syrian military withdrawal on the Lebanese state in the realm of security. Briefly, the thesis unveils the coexistence of state and non-state groups and the engagement of non-state actors in state-like practices. That is, it assesses the impact of the 2005 Syrian military withdrawal on the Lebanese state to reveal the relationship its new configuration, relationship with non-state actors, and emerging governance practices. In that sense, this thesis pretends to contribute to the larger body of literature on theory of the state by offering a benchmark for state transformation processes in the Global South while paying particular attention to institutional limits, actor’s agency, and security governance.